Effect of high intensity ultrasound on physicochemical and functional properties of aggregated soybean β-conglycinin and glycinin. (March 2015) - Hu, Hao; Cheung, Imelda W.Y.; Pan, Siyi; Li-Chan, Eunice C.Y.
Abstract: The effects of high intensity ultrasound treatment (HUS; 20 kHz at 400 W for 5, 20 or 40 min) on aggregated soybean β-conglycinin (7S) and glycinin (11S) fractions were investigated in this study. HUS decreased turbidity and particle size of 7S in 0.05 M Tris–HCl buffer at pH 7.0, while it increased surface hydrophobicity ( H 0 ), solubility, emulsifying activity (EAI) and emulsion stability (ESI). Similarly, HUS of soybean 11S decreased turbidity while increasing EAI but it had minimal effects on particle size and ESI. The SH groups of both 7S and 11S fractions decreased after HUS. HUS did not change 7S or 11S secondary structure, but it slightly increased the percentage of high molecular-weight aggregates under non-reducing SDS-PAGE, and changed the microenvironment of aromatic and aliphatic side chains as observed by Raman spectroscopy of freeze-dried samples. These findings on physicochemical changes of 11S and especially of 7S proteins induced by HUS treatment may contribute to improved applications of soy proteins in food products. Graphical abstract: Highlights: High intensity ultrasound (HUS) partially dissociated β-conglycinin (7S) aggregates. HUS modified tertiary and quaternary structures of 7S and glycinin (11S). Turbidity, SH group, size, hydrophobicity and emulsifying properties were changed. Secondary structure of 7S and 11S was not significantly altered by HUS. HUS induced changes in the amino acid side chain microenvironment.